Determinants of Choice of Marketing Outlet for Edible Insects among Smallholder Farmers and Traders in Western Kenya - Lydia Akinyi Omondi; Mary Orinda (Turkish Journal of Agriculture: Food Science and Technology)
The edible insect sector has, in recent times, gained significant prominence and attention. Particularly, the government of Kenya has made remarkable steps to achieve a potentially large and valuable edible insect market, with a significant milestone being the passing of regulations on edible insects as a new source of proteins. However, research on the edible insect marketing environment is still indistinct. Therefore, the study sought to evaluate the determinants of the market outlets preferred or used by smallholder farmers and traders of domesticated and field-collected edible insects (including cricket, bees, winged termites, lake flies, and dung beetle) in Siaya and Vihiga counties. This cross-sectional study was done among 188 edible insects’ farmers and traders. Purposive sampling identified the study area, while snowball sampling reached the study participants. Data was collected using structured questionnaires and analyzed using multinomial logit regression to assess independent-dependent variable relationships, yielding marginal effects. Study findings showed that at 95% confidence interval, the yield was significant to the three outlets used by the farmers. Gender was significant to both institution and open-air markets outlets but insignificant to selling at the farm gate. Age, education level, and experience in marketing were insignificant to all the three market outlets. Marketing training was significant to the institution and open-air markets. The study also showed that farmers and traders had limited choices to sell their edible insect produce, which was majorly affected by yield and age variables. In view of these findings, enhancing edible insect marketing and training through initiatives that would increase production among farmers and breaking the attitudes toward open-air marketing among male farmers is pivotal to the thriving of the novel food enterprise towards achieving food security in the region.